Genetic association analysis of lipid-lowering drug target genes in chronic kidney disease - Zhang, Yi; Ou, Guangyang; Peng, Lei; Pan, Jian; Zhang, Shaohua; Shi, Jianguo (Frontiers in Endocrinology, 2025)
ObjectiveThe impact of lipid-lowering medications on chronic kidney disease (CKD) remains a subject of debate. This Mendelian randomization (MR) study aims to elucidate the potential effects of lipid-lowering drug targets on CKD development.MethodsWe extracted 11 genetic variants encoding targets of lipid-lowering drugs from published genome-wide association study (GWAS) summary statistics, encompassing LDLR, HMGCR, PCSK9, NPC1L1, APOB, ABCG5/ABCG8, LPL, APOC3, ANGPTL3, and PPARA. A Mendelian randomization analysis was conducted targeting these drug-related genes. CKD risk was designated as the primary outcome, while estimated glomerular filtration rate (eGFR) and blood urea nitrogen (BUN) were assessed as secondary outcomes. Additionally, mediation analysis was performed utilizing 731 immune cell phenotypes to identify potential mediators.ResultsThe meta-analysis revealed a significant association between ANGPTL3 inhibitors and a reduced risk of CKD (OR [95% CI] = 0.85 [0.75-0.96]). Conversely, LDLR agonists were significantly linked to an increased risk of CKD (OR [95% CI] = 1.11 [1.02-1.22]). Regarding secondary outcomes, lipid-lowering drugs did not significantly affect eGFR and BUN levels. Mediation analysis indicated that the reduction in CKD risk by ANGPTL3 inhibitors was mediated through modulation of the immune cell phenotype, specifically HLA-DR on CD14+ CD16+ monocytes (Mediated proportion: 4.69%; Mediated effect: -0.00899).ConclusionThrough drug-targeted MR analysis, we identified a causal relationship between lipid-lowering drug targets and CKD. ANGPTL3 and LDLR may represent promising candidate drug targets for CKD treatment.